2016
DOI: 10.2174/1570161114666160625084427
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Evidence for Deterioration in Endothelial Function Following Ticagrelor Treatment Cessation

Abstract: We identified 30 eligible patients with endothelial function assessment pre- and post-ticagrelor cessation (86.7% men, 13.3% with diabetes and 33.3% current smokers; mean age: 63.6±11.5 years). The study's primary endpoint of RHI at Day 5 did not differ significantly compared with RHI at Day 0, 1.69 (1.45-2.23) vs 1.81 (1.59-2.13). ED rate did not differ significantly between Day 5 and Day 0, 40 vs 33.3%, p=0.8, respectively. No differences in RHI or ED rate were observed between Day 2 and Day 0, 1.64 (1.54-2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Furthermore, discontinuation of chronic ticagrelor treatment did not result in decline in endothelial function per se. While this supports the findings of one previous trial 201 , our study examined the subjects with a longer interval after cessation of ticagrelor and longer intervals between examinations, ruling out any possible lingering effect of the medication (additionally confirmed by measurements of platelet inhibition) or conditioning state from previous examinations. Study IV adds substantial knowledge to the growing understanding of the pleiotropic effects of ticagrelor and its possible implications.…”
Section: Effect Of Ticagrelor Treatment On the Endotheliumsupporting
confidence: 88%
“…Furthermore, discontinuation of chronic ticagrelor treatment did not result in decline in endothelial function per se. While this supports the findings of one previous trial 201 , our study examined the subjects with a longer interval after cessation of ticagrelor and longer intervals between examinations, ruling out any possible lingering effect of the medication (additionally confirmed by measurements of platelet inhibition) or conditioning state from previous examinations. Study IV adds substantial knowledge to the growing understanding of the pleiotropic effects of ticagrelor and its possible implications.…”
Section: Effect Of Ticagrelor Treatment On the Endotheliumsupporting
confidence: 88%
“…Whereas some studies showed beneficial effects, [10][11][12][13][14][15] others demonstrated that it had a lack of effect on endothelial function. [16][17][18] Several probable factors, such as comorbidities, and methods to evaluate endothelial function, will be associated with these inconsistent results. Previous studies examined patients with different comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…4,9 While a series of clinical trials investigated the effect of ticagrelor on endothelial function in patients with coronary artery disease (CAD), the results were contradictory. [10][11][12][13][14][15][16][17][18] Probable explanations of these inconsistent findings include different clinical presentations, comorbidities, methods to evaluate endothelial function, timing from the index event, and the various statuses of concomitant medications. In the 2 studies showing a beneficial effect, patients with ACS, not stable angina, in the acute period were enrolled, and the prescription rate of concomitant medications was lower or unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, FMD is known to be highly user dependent since it requires specially trained personnel [ 57 ]. In this study, we employed the non-invasive, easy-to-use and user-independent pulse amplitude tonometry (EndoPAT) which has already extensively been used in several studies assessing endothelial function [ 57 61 ]. In addition, this method adequately depicts the overall health of the endothelium [ 38 , 39 ] which corresponds with the indication of the nutritional product and which emphasizes that the endpoint is not only validated, but also clinically important.…”
Section: Discussionmentioning
confidence: 99%